Real and imagined Greek women in Victorian perceptions of 1821 - Anna Despotopoulou; Mitsi, Efterpi (Journal of Greek Media & Culture, 2021)
The article explores the reception of 1821 in Victorian popular culture, focusing on the representation of Greek women in stories published in contemporary periodicals. The two dominant tropes of Greek womanhood that emerge in popular fiction and poetry published from the 1830s to the 1890s the captive harem slave and the intrepid warrior arouse sympathy for the enslaved women but also evoke liberal ideas on womens national and social roles. These texts foreground the position of Greek women within a nineteenth-century social context and imbue in them virtues and conflicts such as radicalism, the enfranchisement of women and middle-class domesticity that concerned Britain as much as Greece. Greek women, as represented in these stories, construct a Victorian narrative of 1821 and of the Greek nation that oscillates between familiarity and strangeness, freedom and enslavement, real and imaginary. These largely neglected texts challenge traditional definitions of philhellenism, which depended on the legacy of ancient Greece as justification for the cause of the countrys liberation, and instead construct new myths about Greece, participating in the discursive production of its national fantasy. They also provide the opportunity of reconsidering the cultural position of Modern Greece in the Victorian period beyond the division between Hellenism and Orientalism.